Assessment of standard precaution related to infection prevention readiness of healthcare facilities in Bangladesh: Findings from a national cross-sectional survey. Issue 1 (9th December 2021) - Jubayer Biswas, Md Abdullah Al; Hassan, Md Zakiul; Monjur, Mohammad Riashad; Islam, Md Saiful; Rahman, Aninda; Akhtar, Zubair; Chowdhury, Fahmida; Banu, Sayera; Homaira, Nusrat
Abstract: Background: Baseline assessment of standard precaution relating to infection prevention and control (IPC) preparedness to fight health crisis within healthcare facilities at different levels and its associated factors in Bangladesh remains unknown. Methods: We analyzed the nationally representative Bangladesh health facility survey (BHFS) data conducted by the Ministry of Health and Family Welfare (MoHFW) during July–October 2017. We used the World Health Organization (WHO) Service Availability and Readiness Assessment (SARA) manual to determine the standard precautions related to the IPC readiness index. Using a conceptual framework and multivariable linear regression, we identified the factors associated with the readiness index. Results: We analyzed data for 1, 524 surveyed healthcare facilities. On average, only 44% of the standard precaution elements were available in all facilities. Essential elements, such as guidelines for standard precautions (30%), hand-washing soap (29%), and pedal bins (38%), were not readily available in all facilities. The tuberculosis service area was least prepared, with 85% of elements required for standard precaution deficient in all facilities. Significantly lower readiness indexes were observed in the rural healthcare facilities (mean difference, −13.2), healthcare facilities administered by the MoHFW (mean difference, −7.8), and private facilities (mean difference, −10.1) compared to corresponding reference categories. Conclusions: Our study revealed a severe lack of standard precaution elements in most healthcare facilities, particularly in rural health centers. These data can provide a baseline from which to measure improvement in infection prevention and control (IPC) in these facilities and to identify areas of gaps for targeted interventions to improve IPC strategies that can improve the Bangladesh health system.